2014
DOI: 10.1371/journal.pone.0087133
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting the Intrinsically Disordered Structural Ensemble of α-Synuclein by Small Molecules as a Potential Therapeutic Strategy for Parkinson’s Disease

Abstract: The misfolding of intrinsically disordered proteins such as α-synuclein, tau and the Aβ peptide has been associated with many highly debilitating neurodegenerative syndromes including Parkinson’s and Alzheimer’s diseases. Therapeutic targeting of the monomeric state of such intrinsically disordered proteins by small molecules has, however, been a major challenge because of their heterogeneous conformational properties. We show here that a combination of computational and experimental techniques has led to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 68 publications
(132 reference statements)
6
133
0
Order By: Relevance
“…1A), an intrinsically disordered protein expressed at high levels in the brain, is closely associated with the pathogenesis of a variety of neurodegenerative disorders, collectively known as α-synucleinopathies, including Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple-system atrophy (MSA) (1)(2)(3)(4)(5)(6)(7). It has been exceptionally challenging, however, to develop effective strategies to suppress the formation of α-synuclein aggregates and their associated toxicity (8,9), because the mechanism of aggregation of this protein is extremely complex and highly dependent on environmental factors, such as pH, temperature, and contact with surfaces (10). In particular, it is well established that phospholipid binding can accelerate fibril formation (11); moreover, it has recently been shown that such acceleration occurs through the enhancement of the initial primary nucleation step in the aggregation process (12).…”
mentioning
confidence: 99%
“…1A), an intrinsically disordered protein expressed at high levels in the brain, is closely associated with the pathogenesis of a variety of neurodegenerative disorders, collectively known as α-synucleinopathies, including Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple-system atrophy (MSA) (1)(2)(3)(4)(5)(6)(7). It has been exceptionally challenging, however, to develop effective strategies to suppress the formation of α-synuclein aggregates and their associated toxicity (8,9), because the mechanism of aggregation of this protein is extremely complex and highly dependent on environmental factors, such as pH, temperature, and contact with surfaces (10). In particular, it is well established that phospholipid binding can accelerate fibril formation (11); moreover, it has recently been shown that such acceleration occurs through the enhancement of the initial primary nucleation step in the aggregation process (12).…”
mentioning
confidence: 99%
“…Computational unfoldomics is a recently proposed, emerging concept, which identifies metastable structures by simulations coupled with virtual screen of potential inhibitors [53]. In silico high-throughput structure-based docking screen combined with experiments was successfully applied to identify a druggable small molecule which ameliorates SYN-mediated dysfunction in cell models [56]. These studies are promising; however, none of them takes into account the effect of the inhibitors on the physiological functions of IDPs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IDPs have been recent targets for therapeutic strategies for mammalian diseases such as Parkinson's disease. 55 Similarly, IDPs found in plants could be targets for decreasing crops' susceptibility to disease or increasing overall yield. Additional research could focus on identifying key IDP targets for both therapeutics and plant resistance.…”
Section: Resultsmentioning
confidence: 99%